Analisis Pengaruh Motivasi Kerja, Lingkungan Kerja,Dan Kompensasi Terhadap Kinerja Karyawan(Studi Kasus Pada Spbu 44.594.02 Jepara) - Prasetyo Aji, Yudha, Dr. Anton Agus Setyawan, SE., M.Si (2016)
This research was conducted at the gas station with the purpose of knowing the Jepara 44.594.02 influence the motivation of the work, the work environment, employee performance and compensation against the gas station 44.594.02 Jepara individually and simultaneously. Research methods with the use of this type of research is empirical research that is conducted on the basis of experience. The sample used in this study were 32 respondents.Sampling techniques using a simple random sampling method, namely the taking of a sample from a population of members is done at random without regard to existing strata in the population. Analysis tools are used : 1) research instrument test (test validity and Reliability Test), 2) Test the hypothesis (Multiple Linear Regression, the F-test, ttest, and test the coefficient of Determination ( )), 3) A classic Assumption test (test of Normality, test Multikolinieritas and test Heteroskedastisitas) The results of data analysis, the t test: 1) indicates that the value of the result of the count variable t Work Motivation of 3.095, variable work environments of 2.398 and variable Compensation of 3.198 and the value t = 2.048 table, this means that t calculate > t table then Ho denied that there is a significant influence on the motivation of the work, the work environment and compensation against the performance of individual Employees. And based on the test F shows the value F count of 42.067, that number means F count greater than F table so that his decision to reject Ho. Thus simultaneously variable Work Motivation, work environment and compensation significantly affect the satisfaction of the employee's performance. This shows that influence the motivation of the work, the work environment and compensation on performance of employees.